Indian Media and the Struggle for Justice in Bhopal - Sharma, Shalini (Social justice, 2014)
The article focuses on the Indian media's portrayal of the 1984 Union Carbide pesticide plant disaster that occurred in Bhopal, India and its impact on the prosecution for the disaster. Topics include justice administration in India, corporate liability for industrial disasters, and the political economy of the media in India.